Principios de Direccion de Empresa : un analisis de las funciones direcitivas - kooontz, Harold (mcgraw-hill book company, 1961)
It will be of particular interest to policy makers, government officials, researchers, and economists interested in fostering inclusive economic growth in the countries of the region and their deeper integration into the global economy."--BOOK JACKET.